A novel discrete method of shear angle measurement for in-plane shear properties of thermoset prepreg using a point-tracking algorithm. (June 2019) - Pasco, Corentin; Khan, Muhammad; Kendall, Kenneth
Determining accurate in-plane shear properties of dry and prepreg fabrics is dependent upon the correct measurement of actual shear angle values. This paper presents a novel discrete method of shear angle measurement for in-plane shear properties of thermoset prepreg using a point-tracking algorithm. Two different reinforcement forms of woven and unidirectional with the same rapid-cure resin system are used in this study. In-plane shear tests of picture-frame and bias-extension are employed to evaluate the new discrete method under conditions representative of high-volume manufacturing, i.e. fast deformation rate and elevated temperature. This study demonstrates that the proposed discrete method is capable of measuring the shear angle correctly until large shear deformation, unlike traditional methods such as digital image correlation and the pin-jointed network approach. Furthermore, the normalised shear force data presents a better correlation of the two tests based on the actual shear angle measurement obtained from this novel discrete method.